Adobe InDesign CS6 : classroom in a book. - Cruise, John (Classroom in a book., 2012)
Creative professionals seeking the fastest, easiest, most comprehensive way to learn InDesign CS6 choose Adobe InDesign CS6 Classroom in a Book from the Adobe Creative Team. The 16 project-based lessons show readers step-by-step the key techniques for working with InDesign CS6. Readers learn what they need to know to create engaging page layouts using InDesign CS6. This completely revised CS6 edition covers the new tools for adding PDF form fields, linking content, and creating alternative layouts for digital publishing. The companion CD includes all the lesson files that readers need to work along with the book. This thorough, self-paced guide to Adobe InDesign CS6 is ideal for beginning users who want to master the key features of this program. Readers who already have some experience with InDesign can improve their skills and learn InDesign's newest features. "The Classroom in a Book series is by far the best training material on the market. Everything you need to master the software is included: clear explanations of each lesson, step-by-step instructions, and the project files for the students." -Barbara Binder, Adobe Certified Instructor, Rocky Mountain Training Classroom in a Book®, the best-selling series of hands-on software training workbooks, helps you learn the features of Adobe software quickly and easily. Classroom in a Book offers what no other book or training program does-an official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts.